1996
DOI: 10.1117/12.255383
|View full text |Cite
|
Sign up to set email alerts
|

<title>Miniature fiber optic ultrasonic probe</title>

Abstract: We investigate the feasibility of using optical fibre Bragg gratings for the sensing of ultrasonic fields for medical applications. In preliminary experimental investigations, ultrasonic waves with a frequency of 950kHz have been detected with a noise limited pressure resolution of approximately 10.2 atmospheres in a 3kHz measurement bandwidth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 0 publications
3
32
0
Order By: Relevance
“…Traditionally, only the signal reflected from the FBG is monitored for the change in the optical power in intensiometric interrogation methods [6]. However, when using a spectrally dependent light source that is narrower that the FBG (as in a laser), the signal transmitted through the FBG could equally be monitored [7], with the only difference being the direction of the change, i.e.…”
Section: Transmit Reflect Detectionmentioning
confidence: 99%
“…Traditionally, only the signal reflected from the FBG is monitored for the change in the optical power in intensiometric interrogation methods [6]. However, when using a spectrally dependent light source that is narrower that the FBG (as in a laser), the signal transmitted through the FBG could equally be monitored [7], with the only difference being the direction of the change, i.e.…”
Section: Transmit Reflect Detectionmentioning
confidence: 99%
“…However, the use of FBGs as sensors is not limited to pure spectral measurements, there are in fact a number of different filtering methods that can be used to convert the spectral shift of the FBG into an optical power change [11]. Power detection [12], where a laser is tuned to one of the 3dB points of the FBG would require a tunable laser at 850nm, so this would be prohibitive. The linear edge filter detection method would be the most cost effective [13], as it only requires the use of two identical FBGs and one or two photodetector.…”
Section: Sensing Systemsmentioning
confidence: 99%
“…FBG sensors are now widely used in many industries, such as aerospace, civil engineering, composite material, petrochemical engineering and so on [2] . With fast progress in other disciplines and the background of trans-discipline, FBG sensors are gradually found that can be used to detect ultrasound, in place of traditional piezoe-lectric transducer (PZT) sensors [3] . Further, FBG sensors can be developed and used as hydrophones, in structure health monitoring system, ultrasound distance measurement system, etc [4][5][6] .…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%